Pondering Collaborative School Board Roles in Alleviating Dropout among Learners with Physical Disabilities in Schools - Monyane, Mohapi Augustinus; Kgothule, Rantsie (Research in Social Sciences and Technology, 2023)
The present paper explores collaborative school board roles in alleviating dropout among Children with Physical Disabilities (CwPDs) in primary schools in Lesotho. An interpretive approach with a qualitative case study design provided insight into how school board members interpret and understand their roles and responsibilities and shed light on school boards' strategies to alleviate dropout of CwPDs. In-depth individual interviews were conducted to obtain rich and accurate data from 10 participants from two purposively selected mainstream primary schools. Bronfenbrenners' bio-ecological systems theory and Telford's collaborative leadership theory were used in the study. Through a process of thematic analysis, apparent themes emerged. Findings reveal that many school board members lack the necessary knowledge and skills to address the needs of CwPDs. The research concludes that CwPDs drop out of school because of poor infrastructure, ineffective collaboration, and unclear school policies. It is recommended that through forging collaboration between school board members and other role players, a transformation of policies, in-service training for school boards, and raising disability awareness and dropout among CwPDs can be better alleviated.